The potential of agent-based modelling for verification of people trajectories based on smartphone sensor data - Hillen, Florian; Höfle, Bernhard; Ehlers, Michael; Reinartz, Peter (8th International Symposium of the Digital Earth (ISDE8), 2014)
In this paper the potential of smartphone sensor data for verification of people trajectories derived from airborne remote sensing data are investigated and discussed based on simulated test recordings in the city of Osnabrueck, Germany. For this purpose, the airborne imagery is simulated by images taken from a high building with a typical single lens reflex camera. The smartphone data required for the analysis of the potential is simultaneously recorded by test persons on the ground. In a second step, the quality of the smartphone sensor data is evaluated regarding the integration into simulation and modelling approaches. In this context we studied the potential of the agent-based modelling technique concerning the verification of people trajectories.
Gesehen am 26.01.2021